Digitalization of Police Services as Public Service Innovation: A Case Study of the Parepare Police - Ahmad, Jamaluddin; Nurjannah Nonci; Zainuddin, Abdul Majid; Astuti, Yayuk; Gafur, Abdul (Universitas Muhammadiyah Malang, 2026)
This study investigates the digitalization of police services through the Polri Super App at the Parepare Police Department, focusing on efficiency, accessibility barriers, accountability and transparency, and institutional challenges. The research aims to analyze how digital policing contributes to more efficient and accountable service delivery while also identifying the limitations constraining its implementation. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. They were processed using NVivo software to generate thematic coding, word frequency visualization, and a matrix coding query. The findings reveal that the application significantly improved efficiency by reducing waiting times and streamlining administrative processes. It also enhanced accountability through digital trails that minimized manipulation and unofficial payments. However, the study highlights persistent barriers, particularly for older citizens with limited digital literacy, as well as institutional challenges such as inadequate staff training and frequent system downtime. From a theoretical standpoint, the results confirm the relevance of the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). At the same time, the New Public Service (NPS) framework emphasizes the importance of accountability and inclusivity in digital reforms.